Synergistic studies on the removal of dyes by waste (Metroxylon sagu) based activated carbon: an optimization study - Amode, Jeminat Omotayo; Alam, Md Zahangir; Mirza, Aminul Haq; Mei, Chan Cin; Santos, Jose Hernandez (Institute of Physics Publishing, 2018)
Physically activated carbon prepared from untreated (Metroxylon sagu) waste was used as adsorbents for the adsorption studies of methylene blue (MB) and gentian violet (GV) dye in aqueous solution. Response Surface Methodology (RSM) was employed to investigate the different operating parameters on the uptake of the dye molecule. The adsorbent before and after activation process were characterized to determine the specific surface area, iodine value, textural structure, and surface functional group. The results predicted using CCD model showed high values of regression coefficients R2 (MB= 0.9944 and GV= 0.9845) indicating good agreement with experimental data. Characterization of PAC produced also showed that the activation conditions would find good-quality adsorbent with the highest BET surface area of 1423.5 m2/g, iodine value of 1275.2 mg/g and well-forming pores distribution.